Botanical gardens and citizen science: An (as yet) under-exploited potential. (3rd May 2016) - Martellos, S.; Laganis, J.; Bacaro, G.; Bonacquisti, S.; Derewnicka, L.; Attorre, F.
Abstract: Participation of citizens to research activities probably began with a "Christmas bird count" in 1900. Citizen science (CS) activities can aim at several purposes: long-term monitoring, environmental education, preservation of traditional ecological knowledge. Citizen scientists can collect data, support scientists in the field, involve decision-makers, plan new research activities, etc. While CS may have critical issues, especially as far as data quality is concerned, it has several relevant advantages as well (reduced costs, production of "big data", awareness raising, etc.). However, especially in Europe, there is still an under-exploited potential for botanical gardens to act as drivers for CS initiatives.